Low birth weight associations with cardiac structure and function in adults after arterial switch for transposition of the great arteries - Art Schuermans; Béatrice Santens; Jef Van den Eynde; Xander Jacquemyn; Roel L.F. Van der Palen; Michael C. Honigberg; Alexander Van De Bruaene; Piet Claus; Jan Bogaert; Werner Budts (International Journal of Cardiology Congenital Heart Disease)
Background and aims: The objective of this study was to assess the associations of birth weight with cardiac structure and function in adults with dextro-transposition of the great arteries (D-TGA) who underwent the arterial switch operation (ASO). Methods and results: Thirty-nine ASO patients (age 24.4 ± 3.3 years) were included during routine clinical follow-up from July 2019 to December 2021. All patients underwent cardiopulmonary exercise testing and cardiac magnetic resonance imaging at rest and during exercise. Early-life characteristics, including birth weight, were extracted from electronic medical health records. Linear regression analysis showed that lower birth weight was associated with smaller left ventricular (LV) and right ventricular (RV) end-diastolic volume index (LV: −14.5 mL/m2 [95 % confidence interval, CI: −26.5 to −2.5] per 1-kg decrease in birth weight, p = 0.04; RV: −11.2 mL/m2 [-20.7 to −1.7] per 1-kg decrease in birth weight, p = 0.03). Lower birth weight was associated with greater LV and RV ejection fraction at rest (LV: +8.5 % [+4.4 to +12.5] per 1-kg decrease in birth weight, p < 0.001); RV: +8.1 % [+2.8 to +13.4] per 1-kg decrease in birth weight, p = 0.005). Furthermore, lower birth weight was associated with an attenuated increase in LV stroke volume index from rest to peak exercise (−5.2 mL/m2 [-9.3 to −1.2] per 1-kg decrease in birth weight, p = 0.02). Conclusions: Birth weight may be a novel risk factor for adverse cardiac remodeling in adult ASO patients. Further research is needed to delineate the mechanisms underlying the associations between birth weight and cardiac remodeling ASO patients as well as the broader adult CHD population.